Kompetensi lulusan LPTK Islam dan LPTK Umum menurut Stakeholder - Amirah Diniaty; Risnawati Risnawati; Dicki Hartanto (Al-Ulum, 2017)
This article reveals on customer's assessment on alumni competence from Islamic Institute for Teacher Training and General Institute for Teacher Training (LPTK) in the major of English, Chemistry, Mathematics, Economic Education, and Counseling. The research object consisted of 92 alumni who work as the teacher. Research respondents are 24 heads and vice principals in SMA / Madrasah Aliyah and Junior High School / State Junior High School. Data were collected by questionnaire. Data processing with t-test, and got result 0.006 (less than 0,05) which means there is a significant difference on the competence between alumni of the general and Islamic institute of teacher’s training base on customer assessment. The calculation of eta squared got value 0.086 that means there the difference of teacher’s competence is in the middle category.